2015
DOI: 10.1186/s12889-015-2235-y
|View full text |Cite
|
Sign up to set email alerts
|

A dengue outbreak on a floating village at Cat Ba Island in Vietnam

Abstract: BackgroundA dengue outbreak in an ecotourism destination spot in Vietnam, from September to November 2013, impacted a floating village of fishermen on the coastal island of Cat Ba. The outbreak raises questions about how tourism may impact disease spread in rural areas.MethodsEpidemiological data were obtained from the Hai Phong Preventive Medical Center (PMC), including case histories and residential location from all notified dengue cases from this outbreak. All household addresses were geo-located. Knox tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Individuals with frequent travel to other islands, as well as between the islands and the continent, may be considered to be at higher risk for dengue infection. Previous studies of dengue on islands emphasized the importance of preventing the transmission of dengue from the mainland [ 55 ], as well as reintroduction from surrounding islands [ 56 ]. Prior studies of West Nile virus risk in the Galápagos found that the transportation of infected mosquitoes via airplanes was the most likely means that the virus would be introduced to the islands [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with frequent travel to other islands, as well as between the islands and the continent, may be considered to be at higher risk for dengue infection. Previous studies of dengue on islands emphasized the importance of preventing the transmission of dengue from the mainland [ 55 ], as well as reintroduction from surrounding islands [ 56 ]. Prior studies of West Nile virus risk in the Galápagos found that the transportation of infected mosquitoes via airplanes was the most likely means that the virus would be introduced to the islands [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies were divided into 2 categories: (1) articles that presented rural–urban comparison estimates ( n = 37) [ 4 7 , 9 , 25 , 39 , 42 44 , 49 , 53 , 59 62 , 65 , 69 , 72 , 75 , 78 , 83 , 85 , 86 , 88 , 93 , 95 – 97 , 101 , 109 , 119 , 120 , 125 , 126 , 133 , 135 ] and (2) articles that presented rural estimates ( n = 92) [ 4 9 , 19 , 25 , 40 – 71 , 73 78 , 80 – 82 , 84 , 85 , 87 , 89 94 , 97 – 100 , 102 109 , 111 119 , 121 , 122 , 124 132 ,…”
Section: Resultsmentioning
confidence: 99%
“…People at the periphery identified a higher number of risk factors. Common misperceptions included confusion with other febrile diseases, lack of knowledge of transmission mechanisms, and misconceptions about mosquito behavior [79]. There was also in Pak-Ngum community, a lack of depth of knowledge regarding dengue [40].…”
Section: Hostmentioning
confidence: 99%